Glycemic profile of three different insulin regimes during the month of Ramadan - Omar, Mohd Rahman; Muhayidin, Azura Dina; A. Wahab, Norasyikin; Shahar, Mohammad Arif; Wan Seman, Wan Juani; Omar, Ahmad Marzuki; Mustafa, Norlaila; Sukor, Norlela; Kamaruddin, Nor Azmi (Malaysian Endocrine & Metabolic Society (MEMS), 2016)
Introduction: Based on the EPIDIAR study 2001, about 79% of type 2 diabetic Muslims fast, 9.4% of them were on insulin alone and 7.3% on combination with oral antidiabetic agent with the incidence of hypoglycaemia increasing by a ratio of 7 times and hyperglycaemia crisis by 5 times, patients who are on insulin at high risk of acute complications. Aim: To determine the glycaemic profile as well as to evaluate acute complications in particular hypoglycaemia and hyperglycaemia among type 2 diabetic patients who were on 3 insulin regimes during Ramadan.